MAKNA SIMBOLIK PADA PROSESI PERNIKAHAN SUKU SUNDA - Dwi Septiani; Siti Zahra; Alvia Damaroh Agustin (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2024)
The aim of this research is to analyze the symbolic meanings contained in each stage of the Sundanese traditional wedding in Cogreg, Bogor, West Java. This research focuses on the description of the wedding procession from start to finish and reveals the symbolic meanings implied in these traditions or customs. The analysis of this research is in the form of qualitative descriptive. Data collection techniques include interviews and observations. The selected resource person is MA, a trusted individual who often performs traditional Sundanese wedding customs. Through a qualitative descriptive approach, this research explores various processions, such as Mapag Penganten, Ngebageakeun, and seeking blessings, and explains how each step reflects cultural values that bind individuals to their community. The findings reveal that these processions function not only as sacred rituals but also as embodiments of anthropolinguistic values that emphasize the importance of family and community presence in household life. These findings indicate that understanding symbolism in Sundanese weddings is a crucial step to preserving cultural heritage and educating future generations about the importance of cultural perspectives in a broader context